Multiple streams in member state implementation: politics, problem construction and policy paths in Swiss asylum policy - Sager, Fritz; Thomann, Eva (Journal of public policy, 2017)
This article applies the multiple streams approach to a multilevel implementation setting to analyse why Swiss member states enabled the labour market integration of asylum seekers between 2000 and 2003. It argues for integrating the social construction of target groups into the problem stream, and complementing the policy stream with inherited policy paths. A fuzzy-set qualitative comparative analysis reveals that institutionalised policy paths trump politics in explaining the enabling of labour market integration of asylum seekers. Conversely, a weak political left combined with negative problem constructions aces out policy paths in explaining restrictions of labour market integration. The results illustrate how social constructions influence problem framing. Historical institutionalism theory helps us understand how inherited policy logics feed back with actors’ problem perceptions. Because of the parallels in their multilevel systems, political contexts and problem pressures, this historical case offers salient lessons for the refugee crisis in the European Union today.